Survival, movement, and resource selection of male mule deer and white-tailed deer in western Kansas - Kinlan, Maureen Alexandra (Kansas State University, 2021)
Abundance and occupied range of mule deer (Odocoileus hemionus) in Kansas have been declining for 20 years. The two predominant hypotheses for the reduction of mule deer and concurrent expansion of white-tailed deer (O. virginianus) are changes in land use and competitive dominance of white-tailed deer over mule deer. Despite the popularity and income that stem from hunting revenue, there have been no recent studies that provide critical insight on how to improve management and conservation of sympatric populations of either deer species in Kansas. My objectives were to (1) test for differences in annual and weekly survival rates between species, identify temporal mortality patterns, and assess influences of hunting and rut on survival; and (2) examine movement patterns, space use, and population-level resource selection by adult male mule deer and white-tailed deer in western Kansas during three time periods (annually, rut, and 12-day firearm season). I deployed GPS-collared 60 (30 mule; 30 white-tailed deer), 25 (12 mule; 13 white-tailed deer), and 26 (13 mule; 13 white-tailed deer) male mule deer and white-tailed deer at two different study sites (north and south) located in western Kansas in 2018, 2019, and 2020, respectively, maintaining a sample size of 60 at the start of each study year. Each deer was fitted with a high resolution GPS/VHF collar that recorded bi-hourly locations and used an activity sensor to identify mortality events. I assigned each deer to an age class (<3 or ≥3 years old). I analyzed the influence of single variable models (age class, species, study site, year, site and year interaction, and morphological measurements [total body length, chest girth, hind foot, and neck girth]) to identify variables that influenced survival. I calculated average daily and average bi-hourly movement rate for all groups (north mule deer, south mule deer, north white-tailed deer and south white-tailed deer) and analyzed peak movement trends to define the rut periods for each species. I used Biased Random Bridge Movement Models to estimate period home ranges and core use areas by species and sites and tested for species*site interactions. I identified temporal space use of different land cover categories during the annual, rut, and 12-day firearm season periods. I compared used and available proportions of categorical land cover and continuous macro habitat features at second-order resource selection. Annual survival did not differ between species during 2018-2020 (mule deer 0.54 ± 0.05, white-tailed deer 0.58 ± 0.05); pooled survival for combined species was 0.56 ± 0.04. December was the most hazardous time of year for both species. Harvest was the predominant cause of mortality (50% of mortalities [firearm = 42%, archery = 8%]. Other sources of mortality stemmed from natural causes (21%), unknown (25%), and deer-vehicle collisions (4%). Kaplan-Meier cumulative survival results showed that survival of both mule deer and white-tailed deer was affected by harvest season and rut; the two weeks of firearm season heavily reduced survival by 19.6%, and 12.4% for mule deer and white-tailed deer, respectively. Survival was reduced by 10.6% and 9.8% during rut for mule deer and white-tailed deer, respectively. Additionally, site and year interaction (ω = 0.38) was the most parsimonious model for predicting adult male survival, the model site, was also competitive. Localized periods of high mortality occurred; compared to 2018 and 2019, deer survival in the north site during 2020 was drastically lower (0.26 ± 0.09) than other annual species-site combinations. Space use at the landscape scale varied temporally by site and species. Population-level selection of macro habitat differed between species Males reduced both bi-hourly movement rate and daily distance during the 12-day firearm period compared to their rut movements; north mule deer reduced their total daily movement by 35%, south mule deer by 33%, north white-tailed deer by 5% and south white-tailed deer by 32%. Rut (~Nov 5-25 for both species of north deer; ~Oct 29-Nov 18 for south mule deer; ~Oct 29-Nov 25 for south white-tailed deer) begins for both species approximately 3-4 weeks prior to the 12-day firearm period. Peak movement periods occurred during rut simultaneously for both species, with all deer moving at least twice as fast (bi-hourly) and twice as much (in 24 hr. intervals) during their rut seasons compared to their annual movements. Males reduced movement during the 12-day firearm season compared to their rut movements because of the proximity of the successive 12-day firearm season to the post-rut period; a time in which males may move less in an attempt to recover from the physiological demands of rut. Speculatively, hunters on the landscape may have been a contributing factor to the decrease in movement. To combat the current population trajectory of mule deer abundance and augment the management and conservation of mule deer, I suggest decreasing the harvest limit of male mule deer to directly increase annual survival of adult male mule deer.
Keywords: Mule deer; White-tailed deer; Sympatric; Great Plains; Survival; Movement